Organization Culture: Case Study of Siam Commercial Bank Public Company Limited at Amphoe Muang, Khon Kaen - พรรณศิริชัย กรกนก; ออมอด วณิชชา; วันชูพริ้ง ศรีสุดา; วีรวงศ์ไพบูลย์ เสาวภัทร (KKBS Journal of Business Administration and Accountancy, 2018)
The purposes of research were 1) To study the employees’ perception of organization culture of the Siam commercial Bank Public Company Limited at Amphoe Muang, KhonKaen 2) Survey the organization culture of the Siam commercial Bank Public Company Limited at Amphoe Muang, KhonKaen. The research was using questionnaire to collect data gathering from personal of the Siam commercial Bank Public 10 branch office amount 114 persons. Results of the study showed that organization culture model of employees the option is mostly a task oriented culture. Which the results of this research are useful information and guidelines for enhancing employee productivity by creating a good organization culture, effective for the benefit of the administration, operation and competition of organization.